2010
DOI: 10.1186/1617-9625-8-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of primary risk factors for oral cancer from select US states with increasing rates

Abstract: ObjectivesTo examine the primary risk factor for oral cancer in the US, smoking and tobacco use, among the specific US states that experienced short-term increases in oral cancer incidence and mortality.MethodsPopulation-based data on oral cancer morbidity and mortality in the US were obtained from the National Cancer Institute's (NCI) Surveillance, Epidemiology, and End Results (SEER) database for analysis of recent trends. Data were also obtained from the Centers for Disease Control and Prevention (CDC) Beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 33 publications
1
28
0
3
Order By: Relevance
“…The known risk factors for OTC include consumption of all forms of tobacco, excessive alcohol drinking [12,14]. Even though the prevalence of human papilloma virus (HPV) infections related tumors is clearly lower in the oral tongue compared to the oropharynx, up to 6% of oral cavity tumors have been reported to be HPV positive by DNA-PCR [15].…”
Section: Introductionmentioning
confidence: 99%
“…The known risk factors for OTC include consumption of all forms of tobacco, excessive alcohol drinking [12,14]. Even though the prevalence of human papilloma virus (HPV) infections related tumors is clearly lower in the oral tongue compared to the oropharynx, up to 6% of oral cavity tumors have been reported to be HPV positive by DNA-PCR [15].…”
Section: Introductionmentioning
confidence: 99%
“…These activities have been mainly conducted in the United States, where dental professionals may have been aware of the detrimental effects of smokeless tobacco in the oral cavity in their daily practice [5]. However, they are now expanding globally based on evidence of the detrimental effects of smokeless tobacco in the United States and European countries [6,7] and in Central Asia [8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…To this end, a recent pilot study evaluating oral HPV among healthy adults was performed in Nevada [42], a state recently documented with rising rates of oropharyngeal cancers, in stark contrast to the declining rates observed in neighboring states and the US more generally [43,44]. This study revealed the presence of high-risk strain HPV16, but not HPV18, among females and minorities, the only population subgroups demonstrated to have rising orpharyngeal cancer rates – despite the overall declining rates observed within the general population [45-47].…”
Section: Introductionmentioning
confidence: 99%